Sipakatau, Sipakainge, Sipakalebbi: Sebuah Nilai Budaya untuk Upaya Pencegahan Bullying dengan Memaksimalkan Peran Bystander - Andi Halima; Asniar Khumas; Kurniati Zainuddin (Indonesian Psychological Research, 2021)
Bystander plays an important role in the recurrence of bullying episodes, so that they needs to be empowered in order to prevent bullying. bullying prevention need to be culturally sensitive. The values of Sipakatau, Sipakalebbi, Sipakainge appear to be in line with anti-bullying value. This study is a preliminary studies that aimed to find whether those cultural values could encourage the bystander to be actively involved and how to apply them in the social relationships. Therefore, the study used a qualitative method with a semi-structured interview on four bullying defenders. The result showed that the values of Sipakatau, Sipakalebbi, Sipakainge arose in religious values that socialized within family. Sipakatau, Sipakalebbi, Sipakainge were not only recognized as cultural values but also appeared as strategies to intervene bullying. These findings can be suggested to promote the religious and cultural-based association value as a prevention of school bullying. Keyword: Bullying prevention, Sipakatau, Sipakainge, Sipakalebbi, Bystander